Introduction about world agricultural Bank - Kheyrodin, Hamid (Technium EconomiA, 2024)
A type of bank that lends money to farmers for longer periods of time and charges them less interest than other types of banks. In the Paleolithic Levant, 23,000 years ago, cereals cultivation of emmer, barley, and oats has been observed near the sea of Galilee. Rice was domesticated in China between 11,500 and 6,200 BC with the earliest known cultivation from 5,700 BC, followed by mung, soy and azuki beans Agricultural Bank of China, also known as AgBank, is one of the "Big Four" banks in China. It was founded on 10 July 1951, and has its headquarters in Dongcheng District, Beijing. It has branches throughout mainland China, Hong Kong, London, Tokyo, New York, Frankfurt, Sydney, Seoul, and Singapore. This study were examined relationship between BANK CREDITS and investment growth of agricultural in international sector.The results confirm the existence of a long-run relationship between variables in model. In addition, according to the results, bank credit is the most significant variable in explaining the GROWTH INVESTING, so that increases access to it will encourage growth investment of the agricultural sector. The first official agricultural finance institution of Iran was established in 1933.